2023
DOI: 10.1371/journal.pone.0288014
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and production behaviors of Chinese undergraduate EFL learners

Abstract: Psychological factor have received much attention in education research. The present mixed-methods study focuses on the effect of foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA) on production behaviors among 182 Chinese English as a foreign language (EFL) learners in FL teaching classes. The major findings are as follows: (1) Chinese university students prefer written production behaviors to oral ones, and personal or pair-work oral practice to onstage oral demonstrations due to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The POA-R participants showed a very good attitude toward the POA-R teaching approach, as evidenced by the mean scores of 10 out of 14 items in the POA-R group exceeding 4. Wang's research indicates that both teachers and students have a positive attitude towards the POA teaching approach, which is in line with the positive attitudes of POA-R participants examined in this study [36]. Additionally, the supervisors' reflections demonstrated that they had positive opinions of the POA-R teaching approach.…”
Section: Poa-r Teaching Approach Is Recognized By the Students And Th...supporting
confidence: 83%
“…The POA-R participants showed a very good attitude toward the POA-R teaching approach, as evidenced by the mean scores of 10 out of 14 items in the POA-R group exceeding 4. Wang's research indicates that both teachers and students have a positive attitude towards the POA teaching approach, which is in line with the positive attitudes of POA-R participants examined in this study [36]. Additionally, the supervisors' reflections demonstrated that they had positive opinions of the POA-R teaching approach.…”
Section: Poa-r Teaching Approach Is Recognized By the Students And Th...supporting
confidence: 83%